2016
DOI: 10.1016/j.gie.2016.03.1472
|View full text |Cite
|
Sign up to set email alerts
|

A tablet-interfaced high-resolution microendoscope with automated image interpretation for real-time evaluation of esophageal squamous cell neoplasia

Abstract: Background and Aims In recent years, high-resolution microendoscopy (HRME) has shown potential to improve screening for esophageal squamous cell neoplasia (ESCN). Furthering its utility in a clinical setting, especially in lower-resource settings, could be accomplished by reducing the size and cost of the system as well as incorporating the ability of real-time, objective feedback. This article describes a tablet-interfaced HRME with fully automated, real-time image analysis. Methods The performance of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 17 publications
2
75
0
Order By: Relevance
“…Normal squamous epithelium is characterized by regularly spaced, small nuclei. In contrast, the area of HSIL showed larger, more closely spaced nuclei, which is consistent with previous studies using high resolution microendoscopy to study squamous epithelium where increased nuclear density and nuclear size are observed and can be quantified in dysplastic tissue (13,14,31). The DSIMe images corresponding to the HSIL region showed improved image contrast.…”
Section: Resultssupporting
confidence: 90%
“…Normal squamous epithelium is characterized by regularly spaced, small nuclei. In contrast, the area of HSIL showed larger, more closely spaced nuclei, which is consistent with previous studies using high resolution microendoscopy to study squamous epithelium where increased nuclear density and nuclear size are observed and can be quantified in dysplastic tissue (13,14,31). The DSIMe images corresponding to the HSIL region showed improved image contrast.…”
Section: Resultssupporting
confidence: 90%
“…Instrumentation upgrades would entail reducing the size and cost of the systems and reducing the image acquisition times to improve image quality. Additionally, integration into the clinical workflow could be aided by use of tablet-based interfaces, which has been reported in tandem with the HRME (30). Future work will also entail implementing the automated image analysis in real-time in order to investigate how the availability of real-time diagnostic information will impact the clinician’s decision making process.…”
Section: Discussionmentioning
confidence: 99%
“…HRME images for each site were analyzed using an automated image analysis procedure (30). Briefly, the algorithm first identifies regions in the HRME image that are free of areas that are too bright or too dim, adjusts the contrast of the image, and converts the image into a binary image to separate the nuclei from the cytoplasm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal cancer is the sixth leading cause of cancer death worldwide. Most deaths occur in developing countries because of late‐stage diagnosis, and where nearly all cases are esophageal SCC . Lugol's chromoendoscopy is currently considered the gold‐standard screening method to identify SCC during gastroscopy; however, its specificity is low (approximately 70%) whereas its sensitivity is considered >90%.…”
Section: Esophagusmentioning
confidence: 99%